The Role of Self Esteem in Developing Social Anxiety - Calin, Mariana Floricica; Sandu, Mihaela Luminita; Chifoi, Miruna Alexandra (Technium Social Sciences Journal, 2021)
Nowadays, anxiety is a growing phenomenon because people come across more and more stressful situations. Therefore, among its different forms of manifestation, there is social anxiety. This type of anxiety generally starts in adolescence, when personality is still shaping up and when teenagers are more and more interested in getting confirmation from others. When he is analyzed by others, a teenager fears failure and being ashamed when things are not the way they should, he fears being judged by others for possible small mistakes and, thus, anxiety appears. In other words, persons with low self-confidence and lacking confidence in their abilities have low self-esteem and can easily develop a form of anxiety. As we have already mentioned, social anxiety is caused by the fear of being criticized by others, by the fear of being improperly evaluated, by the feeling of being ashamed, of being in the presence of unknown persons, etc. All these social contexts are backgrounds for individuals’ unexplainable restlessness that can lead to physical symptoms such as excessive perspiration, trembling, palpitations, blushing etc. Self-esteem is very important here as it is very important how the subject sees himself or herself in the social situation. Thus, if a person feels unable to deal with situations considered difficult and if there is lack of confidence in her/his own abilities, meaning he/she has low self-esteem, it is highly possible that this behaviour lead to the debut of social anxiety. Therapy sessions help reduce and even eliminate this disturbance. There are certain techniques consisting of facing the problems up to the moment where the subject begins feeling comfortable with normal life aspects which used to be considered anxiety episodes.